Captopril pretreatment augments diabetogenic response to streptozotocin administration: experimental in vivo rat model - Hayam Ateyya; Asmaa Mohammed ShamsEldeen; Sara Adel Hosny; Samaa Samir Kamar; Laila Ahmed Rashed; Abeer Mostafa; Inas Harb (SpringerOpen, 2024)
Abstract Background Streptozotocin (STZ) is a glucose analogue commonly used for inducing diabetes in experimental animals. This study is intended to investigate the ability of captopril (Cap) pretreatment to augment STZ-induced diabetogenic effect in an experimental rat model. If this hypothesis were proven, Cap administration to rats could reduce the dosage of STZ by augmenting its effect and resulting in a subsequent reduction in STZ cost. Forty-two adult male Wistar rats were randomly divided into seven groups: a control group that fed a normal diet, whereas the other six experimental groups were fed a high-fat diet (HFD). The six groups were then divided into STZ-30, STZ-30-Cap, STZ-40, STZ-40-Cap, STZ-50, and STZ-50-Cap. All Cap-received groups were supplemented with 50 mg/kg Cap orally one hour just before intraperitoneal (I.P.) injection of STZ. 30-STZ, 40-STZ, and 50-STZ-treated groups were injected once with STZ I.P. at doses of 30, 40, and 50 mg/kg, respectively. An intraperitoneal glucose tolerance test (IPGTT) was done. Pancreatic tissue was obtained to measure Tumor necrosis factor alpha (TNF-α), interleukin one beta (IL-1β), and nitric oxide (NO) by enzyme-linked immunosorbent assay (ELISA) and glucose transporter 2 (GLUT2) gene expression by reverse transcription polymerase chain reaction (RT-PCR). Pancreatic sections were examined by hematoxylin and eosin (H&E) stain, and immunohistochemical staining by anti-insulin and anti-TNF-α antibodies. Results Results indicated that administration of Cap before STZ in different doses significantly augmented the hyperglycemic state that was evident by intraperitoneal glucose tolerance test, and markedly increased pancreatic pro-inflammatory markers. Histological analysis of islets of Langerhans indicated degeneration with extensive vacuolations associated with a significant decrease in mean area % of insulin immunoreactivity and an increase in optical density of TNF-α immunoreactivity. Conclusion These findings pointed to the ability of captopril pretreatment to augment the hyperglycemic state and the diabetogenic response that was induced secondary to STZ injection in an experimental rat model.